Odpowiedzi

Najlepsza Odpowiedź!
2010-02-20T10:23:21+01:00
A)3(a-2) = 3a-6
b)-4(x+y)= -4x-4y
c)-5(-x+1)= 5x-5
d)-3a(1/3-a)= -a-3a²
e)(t-2s-1)*7= 7t-14s-7
f)1/2(2a-4b+1)=a-2b+1/2
g)m(2m+3)= 2m²+3m
h)3p(2r+5p-1)- 6pr+15p²-3p
i)xy(2x-3y+5)= 2x²y-3xy²+5xy
2010-02-20T10:24:03+01:00
A)3(a-2)=3a-6
b)-4(x+y) = -4x-4y
c)-5(-x+1) =5x-5
d)-3a(1/3-a) =-a+3a^
e)(t-2s-1)*7 =7t-14st-7
f)1/2(2a-4b+1)=a-2b+1/2
g)m(2m+3)=2m^ +3m (^------->oznacza kwadrat)
h)3p(2r+5p-1) =6pr +15p^ -3p
i)xy(2x-3y+5) =2x^y-3xy^ +5xy